Effect of oxygen annealing temperature on properties of spatial atomic layer deposited aluminum-doped zinc oxide films. (October 2021) - Hsu, Chia-Hsun; Geng, Xin-Peng; Wu, Wan-Yu; Zhao, Ming-Jie; Huang, Pao-Hsun; Zhang, Xiao-Ying; Su, Zhan-Bo; Chen, Zi-Rong; Lien, Shui-Yang
Abstract: In this work, spatial atomic layer deposited (sALD) Al-doped ZnO (AZO) films are prepared, followed by an oxygen post annealing process. Effects of annealing temperature on structural, electrical and optical properties are systematically investigated. The experimental results show that the band gap of the films is not much affected by the oxygen annealing temperature. However, the oxygen annealing is able to remove the oxygen vacancies and improve crystalline structure. Annealing at too high temperatures leads to oxygen desorption from the film. The electrical characterization reveals that the resistivity of the sALD AZO films can be tuned in a range of 1.1 × 10 −3 to 1.7 × 10 −2  Ω-cm via oxygen annealing. Graphical abstract: Image 1 Highlights: AZO films are prepared by high-growth rate spatial atomic layer deposition. Oxygen annealing can remove oxygen (vacancies) defects of the Al-doped ZnO films. Resistivity can be tuned from 1.1 × 10 −3 to 1.7 × 10 −2  Ω-cm when annealed at 300–800 °C.